Reconstructing the degree of mammal defaunation throughout the Caatinga - the largest dry tropical forest region of South America - Nathália Fernandes Canassa; Carlos A. Peres; Célia Cristina Clemente Machado; Helder Farias P. Araujo (PLoS ONE, 2025)
Mammal diversity around the world has been increasingly threatened by a myriad of anthropogenic drivers, but particularly overhunting and natural habitat loss. These threats alter the structure of local mammal assemblages and, consequently, their associated ecological interactions. Here, we assess the degree to which the mammal fauna has been defaunated across the 862,818-km 2 Caatinga tropical dry forest region of northeastern Brazil. Specifically, we examine potential changes in the structure of medium- to large-bodied mammal assemblages, large-scale spatial patterns of local extinctions, the loss of ecosystem functionality, and the role of human disturbance and protected areas in mammal defaunation. We compiled empirical data for 51 species representing a total of 73 local mammal assemblages that could be defined as exhaustively sampled throughout the region and compared species distribution estimates between contemporary and historical times. Our results show that 90% of the Caatinga lost between 20% and 80% of its mammal species, and the structure of coexisting local assemblages was further downsized by ~77%. Among all 51 species, 37 lost over 50% of their geographic range across the region. Caatinga defaunation is currently associated with a severe loss of ecosystem functionality. Overhunting, agropastoral habitat conversion and ruminant livestock were the main drivers of the extent and severity of local defaunation rates, which were conversely buffered by protected areas. This study informs conservation efforts in arid tropical forest regions dominated by the rural poor, including protection of remnant dry forests and restoration of mammal- and habitat- mediated ecosystem services.